Beaming as an explanation of the repetition/width relation in FRBs. Issue 3 (22nd July 2020) - Connor, L; Miller, M C; Gardenier, D W
ABSTRACT: It is currently not known if repeating fast radio bursts (FRBs) are fundamentally different from those that have not been seen to repeat. One striking difference between repeaters and apparent non-repeaters in the Canadian Hydrogen Intensity Mapping Experiment sample is that the once-off events are typically shorter in duration than sources that have been detected two or more times. We offer a simple explanation for this discrepancy based on a selection effect due to beamed emission, in which highly beamed FRBs are less easily observed to repeat, but are abundant enough to detect often as once-off events. The explanation predicts that there is a continuous distribution of burst duration – not a static bimodal one – with a correlation between repetition rate and width. Pulse width and opening angle may be related by relativistic effects in shocks, where short-duration bursts have small solid angles due to a large common Lorentz factor. Alternatively, the relationship could be a geometric effect where narrow beams sweep past the observer more quickly, as with pulsars. Our model has implications for the FRB emission mechanism and energy scale, volumetric event rates, and the application of FRBs to cosmology.